1999
DOI: 10.1007/s001270050127
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant drug use in Italy since the introduction of SSRIs: national trends, regional differences and impact on suicide rates

Abstract: Little is known about the use of antidepressant drugs in Italy since the introduction of selective serotonin reuptake inhibitors (SSRIs). To fill this gap, we examined antidepressant drug sales data from 1988 to 1996 for the whole country, and for the years 1995 and 1996 on the regional level. National suicide trends from 1988 to 1994 were also examined to assess whether the increasing use of SSRI antidepressants was associated with changes in suicide rates. From 1988 to 1996 an increase of antidepressant sale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 22 publications
6
77
0
1
Order By: Relevance
“…3 Previous research suggests that national suicide rates declined as SSRI use increased over time in Sweden; similar findings have been obtained for Finland, Norway, and Hungary (Isacsson, 2000;Rihmer et al, 2001;Ohberg et al, 1998). In contrast, Italy did not appear to experience a change in total suicide rates from pre-existing trends following growth in SSRI use (Barbui et al, 1999), while data from Iceland reveals no relationship between the volume of sales of anti-depressant medications more generally and suicide rates (Helgason et al, 2004). ber of children filling prescriptions for anti-depressant medication divided by the number of children receiving medication of any type (p. 979).…”
Section: Introductionmentioning
confidence: 59%
“…3 Previous research suggests that national suicide rates declined as SSRI use increased over time in Sweden; similar findings have been obtained for Finland, Norway, and Hungary (Isacsson, 2000;Rihmer et al, 2001;Ohberg et al, 1998). In contrast, Italy did not appear to experience a change in total suicide rates from pre-existing trends following growth in SSRI use (Barbui et al, 1999), while data from Iceland reveals no relationship between the volume of sales of anti-depressant medications more generally and suicide rates (Helgason et al, 2004). ber of children filling prescriptions for anti-depressant medication divided by the number of children receiving medication of any type (p. 979).…”
Section: Introductionmentioning
confidence: 59%
“…The latest is an analysis by Nakagawa et al (6) showing that the odd trend of increasing suicide in Japan during the 1990s was broken when SSRIs were introduced in 1999, about 10 years later than in Western countries. One Italian (26) and one Icelandic (27) study have failed to demonstrate such a correlation. These studies have been commented on by Isacsson and Rich (2).…”
Section: Relation To Other Studiesmentioning
confidence: 98%
“…Specifically, most of these studies have simply compared suicide rates before and after SSRIs become available in a particular jurisdiction. Studies of Sweden, Finland, Norway, Hungary and Australia using this "interrupted time series" design have found that suicide rates declined as SSRI use increased [Isacsson, 2000;Rihmer et al, 2001;Ohberg et al, 1998;Hall et.al., 2003], although a study in Italy found no effect [Barbui et al, 1999]. Yet the independent effects of SSRI use are difficult to infer from studies that rely on simple before-andafter comparisons within a given country.…”
mentioning
confidence: 99%